2001
DOI: 10.1136/ard.60.12.1123
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise in patients with osteoarthritis of hip or knee: nine months' follow up

Abstract: Objective-To determine whether the effects of an exercise programme in patients with osteoarthritis of hip or knee are sustained at six and nine months' follow up. Methods-A randomised, single blind, clinical trial was conducted in a primary care setting. Patients with osteoarthritis of hip or knee (ACR criteria) were selected. Two intervention groups were compared. Both groups received treatment from their general practitioner, including patient education and drug treatment if necessary. The experimental grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
1
14

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(152 citation statements)
references
References 30 publications
5
132
1
14
Order By: Relevance
“…This was a similar finding to other RCTs which evaluated exercise for hip OA such as graded behavioural exercise 10 , tai chi and hydrotherapy 43 , group-based strengthening 12 and individualised exercise 9,20 . However, some of these studies included people with hip or knee OA 9, 10, 43 , so the evidence regarding the optimal exercise approach for hip OA alone has yet to be identified.…”
Section: Secondary Aimsupporting
confidence: 84%
See 2 more Smart Citations
“…This was a similar finding to other RCTs which evaluated exercise for hip OA such as graded behavioural exercise 10 , tai chi and hydrotherapy 43 , group-based strengthening 12 and individualised exercise 9,20 . However, some of these studies included people with hip or knee OA 9, 10, 43 , so the evidence regarding the optimal exercise approach for hip OA alone has yet to be identified.…”
Section: Secondary Aimsupporting
confidence: 84%
“…4,5 Although ET has demonstrated beneficial effects for hip OA in recommended core outcomes 6 of pain 7,8 and patient perceived improvement (patient global assessment-(PGA) 9,10 in the short and medium term, results for changes in physical function are conflicting. A number of randomised controlled trials (RCTs), some of which have included participants with hip or knee OA, found functional benefits with exercise 9,11,12 , but a meta-analysis, based on data from participants with hip OA only, found no effect on physical function 7 . The small number of participants (n=204) and inter-study heterogeneity may have influenced this finding.…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of the strategies was measured at baseline and 6 weeks via in-person interviews. As continued use of the strategies can decline over time [2,13,19,23,42,43], research staff telephoned participants 24 weeks after enrollment to determine how many days in the last week they practiced the exercises.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of multidisciplinary approaches to managing OA in primary care have investigated trial interventions rather than consultation delivery (22)(23)(24)(25). In a study to identify GP preferences for improving primary care management of OA, approaches such as patient selfmanagement with opportunistic multidisciplinary consultations were considered important and could bring OA in line with the management of other chronic conditions (26).…”
Section: Discussionmentioning
confidence: 99%